Analysis of the influence of Trombe walls on the thermal behavior of Light Steel Frame Construction - Lohmann, Victor Augusto (2020)
Dissertação de Mestrado em Eficiência Acústica e Energética para uma Construção Sustentável apresentada à Faculdade de Ciências e Tecnologia